Ectopic Eruption of First Permanent Molars in Children from North-Western Romania - Rahela Tabita Moca; Raluca Iulia Juncar; Abel Emanuel Moca; Denisa Tabita Sabău; Luminița Ligia Vaida; Mihai Juncar (Diagnostics, 2022)
Ectopic eruption of first permanent molars can lead to complications if left untreated. The aim of this study was to determine the prevalence of the ectopic eruption of first permanent molars in a sample of children from North-Western Romania, and to identify the characteristic of this anomaly in the studied population. We included patients aged between 5 and 9 years, and patients who needed a radiological examination for the diagnosis and treatment of dental or dento-maxillary diseases. The following exclusion criteria were applied: unclear or poor-quality radiographs; radiographs that belonged to patients who benefited from an orthodontic treatment before the panoramic radiograph was taken; patients who were undergoing orthodontic treatment when the radiograph was taken; and patients with local or general diseases that could influence dento-facial growth and development. Three degrees of severity were selected (moderate, severe, and very severe). The sample consisted of 438 patients, and 61 patients were diagnosed with ectopic eruption of first permanent molars (13.92%). Out of the 1752 analyzed molars, 103 were affected (5.87%). Patients with a moderate degree of ectopy were more frequently boys (56%, n = 14), while patients with a severe degree of ectopy were more frequently girls (52.8%, n = 19). Patients with a moderate degree of ectopy had significantly more frequently a unilateral position (57.1%, n = 16), while patients with a very severe degree of ectopy had significantly more frequently a bilateral position (36.4%, n = 12). The ectopic eruption was diagnosed at the level of the upper-right first permanent molar in a percentage of 18.4% (n = 19), at the level of the upper-left first permanent molar in a percentage of 17.5% (n = 18), at the level of the lower-right first permanent molar in a percentage of 32% (n = 33), and at the level of the lower-left first permanent molar in a percentage of 32% (n = 33). Although not very frequent, the ectopic eruption of first permanent molars is an important anomaly that should be early diagnosed, monitored and treated.